ARTICLE ON ANALYZING COLLABORATIVE CARE MODELS IN INTEGRATING PHARMACY SERVICES INTO GENERAL MEDICAL PRACTICE - Hashem Hussain Almakrami, Saleh Hamad Saleh Alyami, Hamad Mahdi Yahya Alzamanan, Musallam Saleh Musallam Alsulayyim, Dhafer Saleh Alsulayyim, Nasser Zaied Balharith, Hamad Ahmad Balharth (Chelonian Research Foundation, 2023)
Collaborative care models integrating pharmacy services into general medical practice have emerged as a promising strategy to enhance patient care and optimize medication management. This article looks at different models of care, including coordinated pharmacy store models, teleconferencing models, and changes in care models. The pharmacist's role in providing compelling pharmaceutical administration and clinical care and understanding instruction is emphasized. The benefits of coordinated pharmacy store administrations include expanded medicine adherence, made strides in clinical results, and fetched reserve funds. To encourage broad utilization, repayment and collaboration must be attended to. The collaborative care demonstration provides a vital system for advancing collaboration and improving well-being outcomes. Keywords Collaborative care models Pharmacy services General medical practice Pharmacists Medication management Interdisciplinary collaboration Medication reconciliation Patient education Medication adherence Healthcare outcomes